Maternal smoking behaviour during pregnancy and the association of Sudden Unexpected Infant Death (SUID): A retrospective cohort study of births in the United States from 2017–2021 - Kiki Hudson; Giulia M. Muraca (PLoS ONE, 2026)
Background Maternal smoking during pregnancy is a significant risk factor for sudden unexpected infant death (SUID). However, the impact of variations in smoking behaviours, including timing, intensity, and cessation, remains understudied. This study examines the association between maternal smoking and SUID, incorporating detailed categorizations of smoking behaviours. Methods We conducted a population-based, retrospective cohort study of live births in the United States from 2017 to 2021 using the Centre for Disease Control Linked Birth-Infant Death files. Maternal smoking was categorized as non-smoking, pre-pregnancy smoking only, trimester-specific smoking, continuous or discontinuous smoking, and cessation before the third trimester, with stratification by smoking intensity. SUID was defined using ICD-10 codes. Multivariable logistic regression was used to estimate unadjusted (OR) and adjusted odds ratios (aOR) for SUID. Sensitivity analyses examined mediation by gestational age and infant birth weight. Results Heavy continuous smokers had the highest aOR for SUID (372.8 per 100,000 births; aOR 2.81, 95% CI 2.67–2.94), followed by light continuous smokers (395.6 per 100,000 births; aOR 2.47, 95% CI 2.19–2.78) and discontinuous heavy smokers (292.5 per 100,000 births; aOR 2.29, 95% CI 1.72–3.00) compared with non-smokers. Pre-pregnancy-only smokers had the lowest odds of SUID among all smoking categories (light: 188.2 per 100,000 births; aOR 1.77, 95% CI 1.48–2.10; heavy: 152.8 per 100,000 births; aOR 1.61, 95% CI 1.44–1.78). In the sensitivity analysis, the natural indirect effect (NIE) of continuous smoking throughout pregnancy on SUID through gestational age and infant birth weight were insignificant (gestational age: β = 1.01, 95% CI 0.99–1.03, p = 0.28, infant birth weight: β = 1.04, 95% CI 0.99–1.08, p = 0.10). Conclusions Maternal smoking significantly influences SUID, with earlier cessation exhibiting weaker associations. These findings emphasize the importance of early smoking cessation interventions to improve SUID outcomes.